Prolyl hydroxylase 2 inactivation enhances glycogen storage and promotes excessive neutrophilic responses - Pranvera Sadiku; Joseph A. Willson; Rebecca S. Dickinson; Fiona Murphy; Alison J. Harris; Amy Lewis; David Sammut; Ananda S. Mirchandani; Eilise Ryan; Emily R. Watts; A.A. Roger Thompson; Helen M. Marriott; et al. (The Journal of Clinical Investigation, 2017)
Fully activated innate immune cells are required for effective responses to infection, but their prompt deactivation and removal are essential for limiting tissue damage. Here, we have identified a critical role for the prolyl hydroxylase enzyme Phd2 in maintaining the balance between appropriate, predominantly neutrophil-mediated pathogen clearance and resolution of the innate immune response. We demonstrate that myeloid-specific loss of Phd2 resulted in an exaggerated inflammatory response to Streptococcus pneumonia, with increases in neutrophil motility, functional capacity, and survival. These enhanced neutrophil responses were dependent upon increases in glycolytic flux and glycogen stores. Systemic administration of a HIF–prolyl hydroxylase inhibitor replicated the Phd2-deficient phenotype of delayed inflammation resolution. Together, these data identify Phd2 as the dominant HIF-hydroxylase in neutrophils under normoxic conditions and link intrinsic regulation of glycolysis and glycogen stores to the resolution of neutrophil-mediated inflammatory responses. These results demonstrate the therapeutic potential of targeting metabolic pathways in the treatment of inflammatory disease.